CRISPR/Cas9-Induced Loss-of-Function Mutation in the Barley Mitogen-Activated Protein Kinase 6 Gene Causes Abnormal Embryo Development Leading to Severely Reduced Grain Germination and Seedling Shootless Phenotype - Křenek, Pavel; Chubar, Elizaveta; Vadovič, Pavol; Ohnoutková, Ludmila; Vlčko, Tomáš; Bergougnoux, Véronique; Cápal, Petr; Ovečka, Miroslav; Šamaj, Jozef (Frontiers in Plant Science, 2021)
Diverse roles of mitogen-activated protein kinases (MAPKs, MPKs) in plant development could be efficiently revealed by reverse genetic studies. In Arabidopsis, mpk6 mutants complete the life cycle, however, they show defects in embryo development leading to raisin-like and burst-out embryo seed phenotypes and abnormal growth and development of seedling roots. A natural rice knock-out mutant in the OsMPK6 gene, a rice orthologue of Arabidopsis MPK6, completes the life cycle but displays dwarfism, erect leaves and small grains. Contrary, T-DNA insertion and CRISPR/Cas9 loss-of-function mutations in OsMPK6 are embryo-lethal causing abortion of embryo development at the globular stage. In this work, we successfully developed a viable transgenic barley line with CRISPR/Cas9-induced monoallelic single base pair CG deletion (WT/-1C) in the third exon of the HvMPK6 gene, a barley orthologue of Arabidopsis and rice MPK6. There were no obvious macroscopic phenotype differences between heterozygous (WT/-1C) plants and control wild type plants. All the seeds collected from heterozygous (WT/-1C) plants were of similar size and appearance. However, seedling emergence percentage (SEP) from these seeds was substantially decreased in the soil in T2 and T3 generation. Mutation analysis of 248 plants showed that none of the emerged plants in T2 and T3 generation was a biallelic mutant in the HvMPK6 gene, suggesting lethality of the -1C/-1C homozygous mutation. The majority of the mutant (-1C/-1C) seeds did not germinate and a minority of them developed into very abnormal seedlings with shootless phenotype in the soil. Mutant seeds contained late-stage developed abnormal embryos with morphologically obvious scutellum and root part of the embryonic axis, but missing or severely reduced shoot part of the embryonic axis. Observed embryonic abnormalities correlated well with seedling shootless phenotype and suggested that the later defect is determined already during the embryo development. Taken together, phenotype abnormalities of the barley mpk6 mutant were different from those of Arabidopsis and rice mpk6 mutants, indicating partially diverse roles of MPK6 in the embryo, seed and seedling development in different plant species.